Den første grønlandske krimi: Et glokalt udtryk - Hejlsted, Annemette (Grønlandsk Kultur- og Samfundsforskning, 2024)
On 8 September 2010, the first Greenlandic crime novel was published by Greenlandic publishers Atuagkat. The novel, entitled The Tattooed Message, is written by the Greenlandic author Kristian Olsen, better known as ‘aaju’. This article examines how The Tattooed Message utilizes the genre(s) of crime fiction and how Greenlandic culture is embedded in the narrative structure of the novel. The article has a glocal double perspective: A global one that asserts the novel’s use of crime fiction genre conventions and a local perspective that highlights the novel’s Greenlandic point of departure, while at the same time demonstrating how the two perspectives are structurally interconnected. The article begins with an explanation of the prevailing genre conventions of crime fiction followed by an analysis of The Tattooed Message showing how Greenlandic culture is intertwined in the novel and rooted in its literariness and plot.